PRIYAYI DAN FASHION; PERUBAHAN CARA BERPAKAIAN PRIYAYI KECIL SURAKARTA 1900-1920 - Muhammad Misbahuddin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2021)
Clothing is not limited to fabrics that cover the body. For a long time it took even centuries, especially when people started to recognize civilization. Clothing became an extension of the social body in their social life. In Javanese culture, self-esteem is in words, while body honor is in clothing. It's just that this phrase is only used by the elite in Surakarta and doesn't apply to ordinary people. At the beginning of the 20th century, along with the rise of the common people to the upper middle class, the struggle for elite status was fought through the wearing of clothes. Using historical methods of analysis and multidimensional approaches, the author attempts to demonstrate the complexity of the struggle of ordinary people to reach the position of the upper middle class by wearing clothes. The sacralization of clothing, long lauded by the elite, began to de-sacralize at the beginning of the 20th century. De-sacralization is symbolized by the elegant and elegant posture of the little Surakarta priyayi. This attitude has an ambiguous impact on the social reality in which new civic experiences arise in society.